Chinese experience on comparison of clinical efficacy and safety of hemodialysis and peritoneal dialysis in the treatment of diabetic kidney failure: a systematic review and meta-analysis - Wei, Zhifeng; Jin, Yujie; Cheng, Jinxiu; Han, Xiaoli; Liu, Junfen; Liu, Shengjun (Frontiers in Medicine, 2023)
Objective: This meta-analysis aims to compare the efficacy and safety of peritoneal dialysis (PD) and hemodialysis (HD) in the treatment of diabetic kidney failure. Methods: Five databases were selected to retrieve research on PD and HD for diabetic kidney failure until August 6, 2022. A fixed-effects or random-effects model was utilized to calculate the standardized mean difference (SMD) or odds ratio (OR) based on the heterogeneity among studies. Results: Sixteen studies were included. The results showed that patients with diabetic kidney failure treated with PD had lower levels of albumin, total protein, and systolic blood pressure (SBP) and higher levels of urine volume, creatinine, and blood urea nitrogen (BUN) and lower risk of cardiovascular and bleeding events, with significant statistical difference when compared with patients treated with HD (albumin: SMD = -1.22, 95%CI: -1.53, -0.91; total protein: SMD = -0.96, 95%CI: -1.16, -0.77; SBP: SMD = -0.35, 95%CI: -0.64, -0.06; urine volume: SMD = 0.68, 95%CI: 0.40, 0.96; creatinine: SMD = 0.49, 95%CI: 0.27, 0.72; BUN: SMD = 0.55, 95%CI: 0.25, 0.85; cardiovascular events: OR = 0.42, 95%CI: 0.28, 0.62; bleeding: OR = 0.41, 95%CI 0.27, 0.62). Conclusions: This meta-analysis summarized the advantages and disadvantages of PD and HD for treating diabetic kidney failure patients. Compared with HD, PD is more effective in preserving residual kidney function, reducing hemodynamic effect, and lowering the risk of bleeding and cardiovascular events in diabetic kidney failure patients, but it also predisposes to protein-energy malnutrition and increases the risk of infection.